Attenuated Oxidative Stress following Acute Exhaustive Swimming Exercise Was Accompanied with Modified Gene Expression Profiles of Apoptosis in the Skeletal Muscle of Mice. (10th April 2016) - Sun, Yi; Cui, Di; Zhang, Zhe; Zhang, Tan; Shi, Jun; Jin, Haixiu; Ge, Zhe; Ji, Liu; Ding, Shuzhe
Abstract : Purpose . The purpose of the present study was to investigate the effect of acute exhaustive swimming exercise on apoptosis in the skeletal muscle of mice. Method . C57BL/6 mice were averagely divided into seven groups. One group was used as control (C), while the remaining six groups went through one-time exhaustive swimming exercise and were terminated at 0 h, 2 h, 6 h, 12 h, 24 h, and 48 h upon completion of exercise. Result . ABTS was significantly lowered at 12 h and 48 h after exercise. The MDA level was significantly decreased at any time points sampled following exercise. Total SOD activity was significantly decreased at 6 h, 12 h, 24 h, and 48 h after exercise. Neither mRNA of Bax nor Bax/Bcl-2 ratio was significantly altered by exercise. mRNA of Bcl-2 was significantly decreased since 6 h after exercise. mRNA and protein expressions of PGC-1 α were significantly increased at different time points following exercise. Conclusion . Cellular oxidative stress level was decreased following low intensity, long duration acute exhaustive swimming exercise in mice, and the enzymatic antioxidant capacity was compromised. Apoptosis of the skeletal muscle was inhibited, which could partially be explained by the enhanced level of PGC-1 α .